Uji Vigor Dan Viabilitas Benih Jagung ( Zea maysL.) Lokal Putih Pada Beberapa Metode Penyimpanan Tradisisional Di Kabupaten Timor Tengah Utara - Asep Ikhsan Gumelar; Anna Tefa; Religius Kenjam (Paspalum: Jurnal Ilmiah Pertanian, 2022)
Corn (Zea mays L.) is one of the agricultural products whose seeds are used for food. Therefore, a good storage method is needed in order to increase the percentage of seed quality. Storage is one of a series of activities carried out after harvest which aims to reduce or reduce seed moisture content and can also increase the vigor resistance and viability of seeds to the environment. There are two types of storage methods, namely traditional storage methods and modern storage methods. The modern storage method is a development of the traditional development method, only the tools and materials used are different. the lowest percentage germination rate of the six parameters observed was the traditional storage method in jerry cans. This means that the percentage of seed germination rates from the four methods with increased germination rate (>) is in accordance with the observed data even though the seed storage period is at the same time, namely from May to September.